Anxiety in acute myocardial infarction survivors - Aneta Spasovska Trajanovska; Jorgo Kostov; Sevime Sallahi Pasholli (SHMSHM / AAMD, 2020)
Introduction :Data obtained in some studies indicate that somatic disorders, in a certain percentage, are associated with a mental health problems, whether in a form of two co-existent diseases, whether psychological problems are only associated symptoms and/or response to somatic disease. Anxiety is psychological symptoms frequently encountered in patients suffering from acute myocardial infarct (AMI). The AIM of our study was to determine the percentage of anxiety in two investigated groups of patients with myocardial infarction and to determinate the correlation between socio-demographic characteristic and level of anxiety in survivors of AMI. Material and methods: The study was designed as observation cross-section including 80 patients treated at the university Clinic of Cardiology Skopje , observed as 2 groups : group 1 was presented with patients during hospitalization for AMI, and 2 group were patients survivors after 6 months of the acute coronary event. Anxiety status was assessed using HAMA scale. Results : The two groups of patients did not show significant difference according distribution of gender , smoking , physical activity, stress , age, mean HAMA , BMI , age of education and marital status . In the first group 21 (51,2%) of patients have anxiety symptoms while in second group 25 (64,1%). In our study acute MI was more prevalent in a men but women had a higher risk of anxiety disorders 27,3% v.s (22,7%). In examination groups the anxiety (HAMA score) was positive correlate with socio-demographic and clinical parameters where only we got negative correlate between anxiety with marital status and BMI in the first group and negative correlation with married status, smoking status, physical activity, stress and BMI in the second group . .Conclusion: The results in our study showed indicative representation of anxiety in patients survivors of AMI. So screening for anxiety in all AMI patients is also important because this patients should be treated differently than those who are not anxiety.
Keywords: patients; myocardial infarction; anxiety; therapy